PENERAPAN QUIZIZ SEBAGAI MEDIA EVALUASI INTERAKTIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS V PADA PELAJARAN BAHASA INDONESIA - Nur Afiatun; Achmad Ramadhan; Oktarafikayanti (EDU RESEARCH, 2024)
This study aims to analyze the application of Quizizz as an interactive evaluation medium to enhance the motivation and learning outcomes of fifth-grade students in Indonesian language lessons. The research method employed is classroom action research (CAR) with two cycles, involving 30 students. The findings indicate that the use of Quizizz significantly boosts students' learning motivation, as reflected in the increased motivation questionnaire scores. Furthermore, the average student score improved from 72 in the first cycle to 80 in the second cycle, with the percentage of students meeting the Minimum Completeness Criteria (KKM) rising from 65% to 88%. These results demonstrate that Quizizz is effective in creating an engaging and enjoyable learning environment, thus aiding students in better understanding the subject matter. This study recommends the use of technology-based evaluation media like Quizizz to enhance the quality of education in elementary schools.